2020
DOI: 10.1111/jjns.12348
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of life‐behavior‐promoting mobilization care with walking‐only mobilization care in post‐gastrointestinal surgery patients: A quasi‐experimental study

Abstract: This study evaluated the effects of a new form of mobilization care called life-behavior-promotion care by comparing its effectiveness with that of conventional mobilization care, which promotes only walking. Methods: This was a quasi-experimental study that non-randomly allocated post-gastrointestinal surgery patients from a surgical ward into two groups: conventional care and life-behavior-promotion care. The participants received their respective care from ward nurses for the first 3 postoperative days and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Several interventions to increase postoperative physical activity were studied, often with limited success 84–91 . One randomized trial investigating a targeted step count intervention showed no difference in duration of hospital stay and increased fatigue scores in patients with a wearable fitness tracker 92 .…”
Section: Resultsmentioning
confidence: 99%
“…Several interventions to increase postoperative physical activity were studied, often with limited success 84–91 . One randomized trial investigating a targeted step count intervention showed no difference in duration of hospital stay and increased fatigue scores in patients with a wearable fitness tracker 92 .…”
Section: Resultsmentioning
confidence: 99%